Paramedic Identification of Pediatric Seizures: A Prospective Cohort Study. (31st August 2021) - Abramson, Tiffany M.; Rose, Emily; Crow, Elizabeth; Lane, Christianne Joy; Kearl, Yvette; Loza-Gomez, Angelica
Abstract: Objective: Pediatric seizures commonly trigger emergency medical services (EMS) activation and account for approximately 5–15% of all pediatric 911-EMS calls. More than 50% of children with active seizure activity do not receive prehospital antiepileptic drugs, potentially because they are not recognized by EMS. The purpose of this study is to evaluate specificity and sensitivity of paramedic identification of pediatric seizures and to describe the characteristics of unrecognized seizures. Methods: This is an 18-month prospective cohort study at a single, pediatric emergency department (ED). EMS patients ≤15 years old with a prehospital provider impression of seizure were included. Upon ED arrival, a data collection form, which included the EMS verbal report and patient's clinical status, was completed by the attending emergency physician. The primary outcome was sensitivity and specificity of paramedic identification of active seizure. Secondary outcomes included characteristics of missed seizures, ED interventions, and disposition. Descriptive statistics, sensitivity, and specificity were computed. Patient characteristics and clinical outcomes were compared. Results: Surveys were completed for 349 patients (Median 3, IQR = 3.4). Fifty-two of the patients (15%) were actively seizing upon arrival at the ED. Sensitivity was 54% and specificity was 96% for paramedic identification of active seizure. Common features of missed cases were abnormal vital signs (75%), gaze deviation (50%) and clenched jaw (33%). Of these, 37% required intubation and 53% were admitted to the intensive care unit. Conclusion: Paramedics were highly specific, but not sensitive in identifying active seizures on ED arrival. Patients with unrecognized seizures presented most commonly with abnormal vital signs and gaze deviation.